Synthesis, Characterization and Antibacterial Activity of DEAE-C Loaded Cefixime Nano-Particles Against Resistant Bacterial Strains - Muhammad Tayyub Kazam; Saman Arooj; Mahpara Tabassum; Hamid Saeed; Mehwish Iqtedar; Nadeem Ahmad; Muhammad Islam; Muhammad Fawad Rasool; Muhammad Usama; Aleena Maryam (Journal of Pharmaceutical Innovation, 2026)

Understanding Quaternary paleoclimatic shifts and their impact on hominin settlement in the lower Soan Valley, sub-Himalayas - Nadir Fawad; Zhongbo Wang; Daidu Fan; Christopher J. Bae; Muhammad Kamran (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Vitamin D Promotes Neuronal Survival via Nrf2 Upregulation in D-Galactose–Induced Mice: An In-Vivo and In-Silico Study - Fawad Ali Shah; Muhammad Zakria; Faten F. Bin Dayel; Najeeb Ur Rehman; Sarwat Jahan; Muhammad Ikram (Journal of Neuroimmune Pharmacology, 2026)

Effect of storage conditions on phytochemical characteristics and activities of black tea cultivated from geographically different landscapes - Syed Ali Raza Naqvi; Sumaira Naz; Muhammad Irfan; Ameer Fawad Zahoor; Atif Hussain Randhawa; João Miguel Rocha; Mohamed Fawzy Ramadan (South African Journal of Botany, 2026)

Linking nitrogen transformations and soil δ15N to assess drivers of nitrogen losses across a tropical peat swamp forest and an oil palm plantation - Elizabeth Gachibu Wangari; Kien Yung Teo; Ricky Mwangada Mwanake; Faustina Elfrida Sangok; Herman Umbau Lindang; Auldry Chaddy; Sharon Yu Ling Lau; Fawad Khan; Nur Azima Busman; Kim San Lo; Hanna Vahter; Muhammad Kamil-Sardar; et al. (Journal of Environmental Management, 2026)

Integrating Nanotechnology and Bioremediation for Efficient Heavy Metals Removal in Aquatic Ecosystems: A Comprehensive Review - Nadia Yasin; Syed Makhdoom Hussain; Shafaqat Ali; Ameer Fawad Zahoor; Abdulrahman Alasmari; Muhammad Munir; Muhammad Asrar; Muhammad Mudassar Shahzad; Adan Naeem (Water, Air, & Soil Pollution, 2026)

The binding effect of biochar with polycyclic aromatic hydrocarbons and their derivatives: Role in carbon sequestration and pollutant removal efficiency - Muhammad Fawad; Lingyu Zhang; Abdelrahman Ibrahim; Xinyi Xu; Tong Wu; Miao Han; Vishnu D. Rajput; Chao Qin; Wanting Ling (Journal of Environmental Management, 2026)

Recent Advances in p-Type Nickel Oxide (NiO) for Solar-Light-Driven Photocatalytic Degradation of Organic Pollutants - Mansoor sultan; Nisar Ali; Muhammad Naseem; Shah Ihsan; Mazharul islam; Abdul kareem; Shahbaz Khan; Bakht Muhammad Khan; Fawad khan; Farman Ali; Adnan Khan; Rayya Ahmed Al Balushi; et al. (Water, Air, & Soil Pollution, 2026)

Protective potential of linalool against cyclophosphamide-induced interstitial cystitis: mechanistic insights from experimental and computational approaches - Irfan Anjum; Asfia Arooje; Saima; Fawad Naeem; Muhammad Naveed Mushtaq; Kashif Barkat; Zaka Ur Rehman; Syed Damin Abbas Hamdani; Shah Jahan; Mohammed Dauelbait; Amir Bouallegue; Esmael M. Alyami; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Pharmacological investigation of natural compounds for therapeutic potential in neuropathic pain - Muhammad Faheem; Arif-ullah Khan; Fawad Ali Shah (Natural Product Research, 2026)

Level-crossing processing and deep convolutional neural network for arrhythmia classification in telehealth services - Syed Fawad Hussain; Saeed Mian Qaisar; Muhammad Sherjeel (Physical and Engineering Sciences in Medicine, 2026)

Microfacies and diagenetic synthesis of the late early-middle eocene Kirthar Formation, Waziristan, Pakistan: implications for reservoir characterization - Fawad Ahmed; Abdullah Khan; Nowrad Ali; Muhammad Zafar; Ihtisham-ul-Haq; Mujahid Ahmed Khan (Carbonates and Evaporites, 2026)

Radon concentration, its deterministic and probabilistic health risks through groundwater consumption, and spatial distribution - Said Muhammad; Fawad Hussain; Saeeda Yousaf; Zafar Iqbal; Umar Farooq; Ashfaq Ahmad (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Advancing carbon dioxide mineralization for long-term carbon storage: Opportunities, challenges, and strategic recommendations - Zahrah Ghannam; Muhammad Shahzad Kamal; Mohamed Mahmoud; Manzar Fawad; Mobeen Murtaza; Muhammad Ali; Shirish Patil (Gas Science and Engineering, 2026)

Ambroxol’s Role in PTZ-Induced Anxiety-Like Conditions in Mice: Targeting Neuroinflammation and Oxidative Stress via In Vivo and In Silico Approaches - Hafeeza Zafar Ali; Sarwat Jahan; Laila Ilahi; Sami Siraj; Muhammad Zakria; Najeeb Ullah; Muhammad Ikram; Ashraf Ullah Khan; Manzoor Khan; Fawad Ali Shah; Hafsah Muhammad (Molecular Neurobiology, 2026)

Bentonite clay in aflatoxin mitigation: advances, efficiency and perspectives - Syed Ali Raza Naqvi; Muhammad Kaleem Khan Khosa; Ameer Fawad Zahoor; Matloob Ahmad; Ariba Abdullah; Muhammad Ramzan Saeed Ashraf Janjua; Syed Ansar Abidi; Fatma Mohamed Ameen Khalil; Mohamed Fawzy Ramadan; João Miguel Rocha (Archives of Microbiology, 2026)

Ameliorating CO₂ capture performance of PEI/PES hybrid membranes via integration of zeolitic imidazolate frameworks - Sadia Sagar; Aqib Riaz; Farzana Siddique; Aysha Siddiqa; Mohsin Ali; Mahnoor Asif; Muhammad Waqas Iqbal; Fawad Inam (Journal of Environmental Chemical Engineering, 2025)

Genomic insights into autosomal recessive epilepsy: novel pathogenic variants in ITPA and CLN5 identified in consanguineous families - Anees Muhammad; Fawad Inayat; Bilal Ahmad Sethi; Muhammad Kashif; Assad Ullah Khan; Shahzad Ahmad; Amir Atlas; Shoaib Ur Rehman; Muhammad Tahir Sarwar (Molecular Biology Reports, 2025)

Identification of mutation in ASPM gene in microcephaly families from Khyber Pakhtunkhwa. - Arsalan Waqas Ahmad Shah; Laraib Shah; Fawad Inayat; Maliha Rabbi; Muhammad Jawad Ullah (Molecular Biology Reports, 2025)

Halotolerant Bacillus Aryabhattai Strain PM34 Mitigates Salinity Stress and Enhances the Physiology and Growth of Maize - Muhammad Atif Azeem; Salman Khan; Fawad Ali; Sajjad Ahmad; Gul Rahim; Muhammad Iftikhar; Majid Iqbal; Rawa Saad Aljaloud; Khaloud Mohammed Alarjani; Hassan Javed Chaudhary (Journal of Plant Growth Regulation, 2025)

Optimizing aquaculture sustainability: Microalgae-based co-culture systems for aquaculture wastewater treatment and pollution reduction - Javaeria Maqsood Gill; Syed Makhdoom Hussain; Shafaqat Ali; Ameer Fawad Zahoor; Abdulrahman Alasmari; Muhammad Munir; Eman Naeem; Muhammad Amjad; Zeeshan Yousaf; Muhammad Faisal (Algal Research, 2025)

A Critical Review of Physiologically Based Pharmacokinetic (PBPK) Models in Liver Cirrhosis - Hafsa Hafsa; Muhammad Fawad Rasool; Faleh Alqahtani (Current Pharmacology Reports, 2025)

Ring opening of epoxides: a facile approach towards the synthesis of polyketides and related stereoenriched natural products: a review - Madiha Hanif; Asim Mansha; Kulsoom Ghulam Ali; Muhammad Athar Saeed; Shahid Mahmood; Aijaz Rasool Chaudhry; Ahmad Irfan; Aqsa Mushtaq; Ameer Fawad Zahoor (Molecular Diversity, 2025)

Epigenetic horizons in aquaculture: unlocking sustainable fish production - Khalid Hussain; Syed Makhdoom Hussain; Shafaqat Ali; Ameer Fawad Zahoor; Ebru Yilmaz; Abdulrahman Alasmari; Muhammad Munir; Muhammad Zubair-ul-Hassan Arsalan; Adan Naeem (Fish Physiology and Biochemistry, 2025)

New paradigms to evaluate the stratigraphy for the geological and geoarchaeological prospects of the upper and post-Siwaliks in the Soan Valley, Upper Indus Basin, Pakistan - Nadir Fawad; Daidu Fan; Taixun Liu; Anne Dambricourt Malassé; Muhammad Kamran; Qazi Adnan Ahmed; Fahad Ali (Quaternary International, 2025)

Comparative efficacy of combined myo-inositol and D-chiro inositol versus metformin across PCOS Phenotypes: enhancing ovarian function, ovulation, and stress response in a prospective clinical trial - Meena Gul; Hina Khan; Bushra Rauf; Syed Murtaza Shah Bukhari; Ehtesham Ehtesham; Muhammad Omar Malik; Fawad Ali Shah; Fawaz E. Alanazi; Mohsin Shah (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Probabilistic seismic loss estimation for residential buildings in Pakistan - Sajid Mehmood; Zainulabideen Ali Khan; Fawad Ahmed Najam; Muhammad Usman (Natural Hazards, 2025)

Status and prospects of omics in lentil: understanding mechanisms and impact on stress breeding under changing climate - Fawad Ali; Yiren Zhao; Arif Ali; Mian Abdur Rehman Arif; Obaid Ullah Shah; Muhammad Atif Azeem; Li Liao; Zhiyong Wang (Journal of Plant Biochemistry and Biotechnology, 2025)

Heavy metals pollution in riverine sediments: Distribution, source, and environmental implications - Kifayatullah Khan; Muhammad Younas; Muhammad Yaseen; Hassan Sher; Afsheen Maryam; Sobhy M. Ibrahim; Adnan Adnan; Ahmad Ali; Muhammad Fawad; Akhtar Zeb Khan; Nasrullah Khan; Izaz Ali Shah (Environmental Monitoring and Assessment, 2025)

Biomitigation of noxious metal ions using engineered lignin-based nanocomposites for sustainable environment - Zaeem Bin Babar; Rashid Iftikhar; Komal Rizwan; Shahid Munir; Mashhood Urfi; Fawad Ashraf; Muhammad Ali Inam; Shahid Iqbal; Muhammad Saad; Sajid Mahmood; Nasser S. Awwad; Hala A. Ibrahium (Journal of Water Process Engineering, 2025)

The role of agricultural land management in modulating water-carbon interplay within dryland ecological systems - Wajid Ali Khattak; Jianfan Sun; Fawad Zaman; Abdul Jalal; Muhammad Shafiq; Sehrish Manan; Rashida Hameed; Ihtisham Khan; Irfan Ullah Khan; Khalid Ali Khan; Daolin Du (Agriculture, Ecosystems & Environment, 2025)

The pivotal role of arbuscular mycorrhizal fungi in enhancing plant biomass and nutrient availability under drought stress conditions: A global meta-analysis - Fawad Zaman; Muhammad Umair Hassan; Wajid Ali Khattak; Ahmad Ali; Mohamed F. Awad; Fu-Sheng Chen (Science of The Total Environment, 2024)

Construction of visible-light-driven 2D/2D NiFe2O4/g-C3N4 Z-scheme heterojunction photocatalyst for effective degradation of organic pollutants and CO2 reduction - Wisal Muhammad; Wajid Ali; Muhammad Asif Khan; Fawad Ali; Amir Zada; Muhammad Zaka Ansar; Pow-Seng Yap (Journal of Environmental Chemical Engineering, 2024)

Enhanced capacity of thiol-functionalized sugarcane bagasse and rice husk biochars for arsenite sorption in aqueous solutions - Israr Masood ul Hasan; Nabeel Khan Niazi; Irshad Bibi; Fazila Younas; Fahad Al-Misned; Muhammad Bilal Shakoor; Fawad Ali; Shazia Ilyas; Muhammad Mahroz Hussain; Jinli Qiao; Andreas Lüttge (Environmental Science and Pollution Research, 2024)
The utilization of biowastes for producing biochar to remove potentially toxic elements from water represents an important pathway for aquatic ecosystem decontamination. Here we explored the significance of thiol-functionalization on sugarcane bagasse biochar (Th/SCB–BC) and rice husk biochar (Th/RH–BC) to enhance arsenite (As(III)) removal capacity from water and compared their efficiency with both pristine biochars (SCB–BC and RH–BC). The maximum As(III) sorption was found on Th/SCB–BC and Th/RH–BC (2.88 and 2.51 mg g −1 , respectively) compared to the SCB–BC and RH–BC (1.51 and 1.40 mg g −1 ). Relatively, a greater percentage of As(III) removal was obtained with Th/SCB–BC and Th/RH–BC (92% and 83%, respectively) at a pH 7 compared to pristine SCB–BC and RH–BC (65% and 55%) at 6 mg L −1 initial As(III) concentration, 2 h contact time and 1 g L −1 sorbent dose. Langmuir ( R 2 = 0.99) isotherm and pseudo-second-order kinetic ( R 2 = 0.99) models provided the best fits to As(III) sorption data. Desorption experiments indicated that the regeneration ability of biochars decreased and it was in the order of Th/SCB–BC (88%) > Th/RH–BC (82%) > SCB–BC (77%) > RH–BC (69%) up to three sorption–desorption cycles. Fourier-transform infrared spectroscopy and X-ray photoelectron spectroscopy results demonstrated that the thiol (-S–H) functional groups were successfully grafted on the surface of two biochars and as such contributed to enhance As(III) removal from water. Spectroscopic data indicated that the surface functional moieties, such as -S–H, − OH, − COOH, and C = O were involved to increase As(III) sorption on thiol-functionalized biochars. This study highlights that thiol-grafting on both biochars, notably on SCB–BC, enhanced their ability to remove As(III) from water, which can be used as an effective technique for the treatment of As from drinking water. Graphical Abstract

Enhancing wheat performance through phosphorus and zinc management strategies under varied irrigation regimes - Abdul Latif Jan; Amanullah; Adil Mihoub; Muhammad Fawad; Muhammad Farhan Saeed; Imad Khan; Emanuele Radicetti; Aftab Jamal (Environment, Development and Sustainability, 2024)

Assessing the health risks of heavy metals and seasonal minerals fluctuations in Camellia sinensis cultivars during their growth seasons - Fawad Zaman; Wajid Ali Khattak; Muhammad Ihtisham; Muhammad Ilyas; Ahmad Ali; Abbas Ali; Haroon Khan; Khalid Ali Khan; Dejiang Ni; Hua Zhao; Fu-Sheng Chen (Food and Chemical Toxicology, 2024)

Occurrence of natural enemies in maize and the predatory potential of selected arthropods against fall armyworm in Multan, Pakistan - Saleem Riaz; Muhammad Ishtiaq; Fawad Zafar Ahmad Khan; Ghulam Ali; Mirza Abid Mehmood; Muhammad Sohail Qamar Zaman (International Journal of Tropical Insect Science, 2024)

Preparation of hierarchically porous zeolite templated carbon from fly ash with investigation into the adsorption behavior towards volatile organic compound - Zhiyuan Liu; Xingxing Cheng; Fawad Muhammad; Jiansheng Zhang (Journal of Environmental Chemical Engineering, 2024)

WITHDRAWN: Valorization of Algal Biomass to Synthesize Heterogeneous gCN-Biochar Photocatalyst for the Treatment of Industrial Wastewater using Photocatalysis-Persulfate Oxidation Process - Aqsa Shafique; Hafiz Muhammad Uzair Ayub; Javed Iqbal; Shanawar Hamid; Fawad Ashraf; Muhammad Saif Ur Rehman; S. Boukhari; Mohamed A. Habila; Alam Nawaz; Tahir Fazal (Chemosphere, 2024)

How ESG reporting is effected by sustainable finance and green innovation: moderating role of sales growth - Fawad Rauf; Wang Wanqiu; Khwaja Naveed; Syed Usman Qadri; Muhammad Sibt e Ali (Environmental Science and Pollution Research, 2023)

Futuristic Streamflow Prediction Based on CMIP6 Scenarios Using Machine Learning Models - Basir Ullah; Muhammad Fawad; Afed Ullah Khan; Sikander Khan Mohamand; Mehran Khan; Muhammad Junaid Iqbal; Jehanzeb Khan (Water Resources Management, 2023)

Cu-doped mesoporous TiO2 photocatalyst for efficient degradation of organic dye via visible light photocatalysis - Sidra Bibi; Syed Sakhawat Shah; Fawad Muhammad; Muhammad Siddiq; Laraib Kiran; Samar A. Aldossari; Mohammed Sheikh Saleh Mushab; Shabnam Sarwar (Chemosphere, 2023)

Retraction notice to “Melatonin rescues the mice brain against cisplatin-induced neurodegeneration, an insight into antioxidant and anti-inflammatory effects” [Neurotoxicology 87 (2021) 1–10] - Muhammad Zakria; Nasir Ahmad; Lina Tariq Al Kury; Abdullah Alattar; Zia Uddin; Sami Siraj; Shakir Ullah; Reem Alshaman; Muhammad Imran Khan; Fawad Ali Shah (NeuroToxicology, 2023)

“Retraction notice to Carveol ameliorates mercury-induced oxidative stress, neuroinflammation, and neurodegeneration in a mouse brain” NeuroToxicology 92 (2022) 212–226 - Abdullah Alattar; Arooj Mohsin Alvi; Sajid Rashid; Nadia Hussain; Mehreen Gul; Muhammad Ikram; Atif Ali Khan Khalil; Reem Alshaman; Fawad Ali Shah; Shupeng Li; Jingbo Li (NeuroToxicology, 2023)

Development of a new base isolation system using the concept of metamaterials - Muhammad Nauman Masoom; Qurat ul Ain Karim; Irtaza Badar; Rao Arsalan Khushnood; Fawad Ahmed Najam; Ahmer Naseer (Engineering Structures, 2023)

Heavy Metal Occurrence, Pathways, and Associated Socio-ecological Risks in Riverine Water: Application of Geographic Information System, Multivariate Statistics, and Risk Assessment Models - Kifayatullah Khan; Muhammad Younas; Muhammad Sajawal Khan; Xu Li; Muhammad Fawad; Noor Samad Shah; Jafar Ali; Sana Ullah; Muhammad Ayaz; Afsheen Maryam; Asmat Ali; Akhtar Zeb Khan; et al. (Water, Air, & Soil Pollution, 2023)

Exploration of plant growth promoting traits and regulatory mechanisms of Bacillus anthracis PM21 in enhancing salt stress tolerance in maize - Muhammad Atif Azeem; Fawad Ali; Abid Ullah; Mahmood Iqbal; Kishwar Ali; Dunia A. Al Farraj; Mohamed S. Elshikh; Qirat Naz; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary (Environmental Science and Pollution Research, 2023)

Do green entrepreneurial orientation and green knowledge management matter in the pursuit of ambidextrous green innovation: A moderated mediation model - Muhammad Usman Shehzad; Jianhua Zhang; Khawaja Fawad Latif; Khalid Jamil; Abdul Hakeem Waseel (Journal of Cleaner Production, 2023)

Clinical pharmacokinetics of terbutaline in humans: a systematic review - Khadeeja Sultan; Ammara Zamir; Waseem Ashraf; Imran Imran; Hamid Saeed; Anees ur Rehman; Abdul Majeed; Muhammad Fawad Rasool (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

The role of various ameliorants on geochemical arsenic distribution and CO2-carbon efflux under paddy soil conditions - Muhammad Mahroz Hussain; Irshad Bibi; Fawad Ali; Zulfiqar Ahmad Saqib; Muhammad Shahid; Nabeel Khan Niazi; Khalid Hussain; Sabry M. Shaheen; Hailong Wang; Qamar Shakil; Jörg Rinklebe (Environmental Geochemistry and Health, 2023)

A hybrid heuristic-driven technique to study the dynamics of savanna ecosystem - Muhammad Fawad Khan; Muhammad Sulaiman; Fahad Sameer Alshammari (Stochastic Environmental Research and Risk Assessment, 2023)

Biochemical Characterization and Potential of Bacillus safensis Strain SCAL1 to Mitigate Heat Stress in Solanum lycopersicum L. - Tehmeena Mukhtar; Fawad Ali; Mazhar Rafique; Javed Ali; Muhammad Siddique Afridi; Donald Smith; Shehzad Mehmood; Amna; Alfred Souleimanov; Ghulam Jellani; Tariq Sultan; Farooq Hussain Munis; et al. (Journal of Plant Growth Regulation, 2023)

An integrated approach towards marble waste management: GIS, SFA, and recycling options - Muhammad Fawad; Farid Ullah; Wisal Shah; Muhammad Jawad; Kifayatullah Khan; Wajid Rashid (Environmental Science and Pollution Research, 2022)

Reverse vaccinology approach for multi-epitope centered vaccine design against delta variant of the SARS-CoV-2 - Khurshid Jalal; Kanwal Khan; Zarrin Basharat; Muhammad Naseer Abbas; Reaz Uddin; Fawad Ali; Saeed Ahmad Khan; Syed Shams ul Hassan (Environmental Science and Pollution Research, 2022)

Assessment of genetic diversity among 131 safflower (Carthamus tinctorius L.) accessions using peroxidase gene polymorphism (POGP) markers - Mehtap Yildiz; Muhammad Tanveer Altaf; Faheem Shehzad Baloch; Metin Koçak; Gökhan Sadık; Cansu Kuzğun; Muhammad Azhar Nadeem; Fawad Ali; Mehmet Bedir; Murat Tunçtürk (Molecular Biology Reports, 2022)

Clean and sustainable transportation through electric vehicles — a user survey of three-wheeler vehicles in Pakistan - Mohammad Aamir Khan; Syed Fawad Bokhari; Aazir Khan; Muhammad Saad Amjad; Arooj Mobasher Butt; Muhammad Zeeshan Rafique (Environmental Science and Pollution Research, 2022)

Marble waste site suitability assessment using the GIS-based AHP model - Muhammad Fawad; Farid Ullah; Muhammad Irshad; Wisal Shah; Qaisar Mahmood; Iqbal Ahmad (Environmental Science and Pollution Research, 2022)

Experimental and theoretical analyses to predict coal and gas outburst using desorption indices of drill cuttings - Barkat Ullah; Yuanping Cheng; Liang Wang; Biao Hu; Izhar Mithal Jiskani; Fawad Ul Hassan; Niaz Muhammad Shahani; Muhammad Ali (Arabian Journal of Geosciences, 2022)

Application of soft computing methods to estimate uniaxial compressive strength and elastic modulus of soft sedimentary rocks - Niaz Muhammad Shahani; Xigui Zheng; Cancan Liu; Peng Li; Fawad Ul Hassan (Arabian Journal of Geosciences, 2022)

Development of green methodologies for Heck, Chan–Lam, Stille and Suzuki cross-coupling reactions - Muhammad Yousaf; Ameer Fawad Zahoor; Rabia Akhtar; Matloob Ahmad; Shazia Naheed (Molecular Diversity, 2020)

Foliage applied proline induces salt tolerance in chili genotypes by regulating photosynthetic attributes, ionic homeostasis, and antioxidant defense mechanisms - Madiha Butt; Abdul Sattar; Tahira Abbas; Ahmad Sher; Muhammad Ijaz; Sami Ul-Allah; Muhammad Rashid Shaheen; Fawad Kaleem (Horticulture, Environment, and Biotechnology, 2020)

Molecular characterization of genetic diversity and similarity centers of safflower accessions with ISSR markers - Fawad Ali; Muhammad Azhar Nadeem; Ephrem Habyarimana; Abdurrahim Yılmaz; Muhammad Amjad Nawaz; Iftikhar Hussain Khalil; Sezai Ercişli; Gyuhwa Chung; Hassan Javed Chaudhary; Faheem Shehzad Baloch (Brazilian Journal of Botany, 2020)

Influence of different organic geo-sorbents on Spinacia oleracea grown in chromite mine-degraded soil: a greenhouse study - Javed Nawab; Nayab Khan; Riaz Ahmed; Sardar Khan; Junaid Ghani; Ziaur Rahman; Fawad Khan; Xiaoping Wang; Juma Muhammad; Hassan Sher (Journal of Soils and Sediments, 2019)

Ciprofloxacin: from infection therapy to molecular imaging - Syed Ali Raza Naqvi; Samina Roohi; Anam Iqbal; Tauqir A. Sherazi; Ameer Fawad Zahoor; Muhammad Imran (Molecular Biology Reports, 2018)

Estimation of wind speed using regional frequency analysis based on linear‐moments - Muhammad Fawad; Ishfaq Ahmad; Falaq Ali Nadeem; Ting Yan; Aamar Abbas (International Journal of Climatology, 2018)
The quantiles of annual maximum wind speed (AMWS) can be estimated for different meteorological stations of interest by using at‐site frequency analysis and extreme value theory. These estimates are of immense importance for the codification of wind speed. However, the historical data of wind speed at the number of meteorological stations are sometimes unavailable and often insufficient due to the shorter length, especially in developing countries like Pakistan. The scarcity of the data increases the uncertainty of the quantiles estimates regarding policy implications. To cope with the problem, an approach of Regional Frequency Analysis (RFA) is opted here. In this study, RFA of AMWS using linear‐moments (L‐moments) is carried out by considering wind speed data of nine meteorological stations of province Punjab, Pakistan. No station is found to be discordant. A single homogenous region is constituted from these nine stations using a subjective approach based on their geographical locations. Heterogeneity measures justify that these nine stations of Punjab form a single homogeneous region. Regional quantiles estimates are found through the most appropriate probability distribution among generalized normal (GNO), generalized logistic (GLO), Pearson Type 3 (P3), generalized Pareto (GPA), Weibull (WEI), log Pearson Type 3 (LP3) and generalized extreme value (GEV) distributions. Z ‐statistic and L‐moment ratio diagram suggest that GLO and GNO distributions are better choices than others. Robustness of both distributions is evaluated through relative bias (RB) and relative root mean square error (RRMSE). Findings indicate that overall, GLO distribution is better than GNO. Further, we also find at‐site quantiles from dimensionless quantities (regional quantiles) using the sample mean and median as scaling factors. Quantiles' estimates calculated from this study can be used in codified structural designs for policy implications.

Effects of water shortage in Kabul River network on the plain areas of Khyber Pakhtunkhwa, Pakistan - Mohammad Nafees; Fawad Ahmad; Muhammad Naeem Butt; Mohammad Khurshed (Environmental Monitoring and Assessment, 2018)

Association of detoxification enzymes with butene-fipronil in larvae and adults of Drosophila melanogaster - Muhammad Shahid Arain; Muhammad Shakeel; Mohammed Esmail Abdalla Elzaki; Muhammad Farooq; Muhammad Hafeez; Muhammad Rafiq Shahid; Syed Ali Haider Shah; Fawad Zafar Ahmad Khan; Qaiser Shakeel; Abdalla Markaz Abdalla Salim; Guo-Qing Li (Environmental Science and Pollution Research, 2018)

Recent trends in ring opening of epoxides with sulfur nucleophiles - Sajjad Ahmad; Ameer Fawad Zahoor; Syed Ali Raza Naqvi; Muhammad Akash (Molecular Diversity, 2018)

Fasting leptin and glucose in normal weight, over weight and obese men and women diabetes patients with and without clinical depression - Darakhshan Jabeen Haleem; Shehnaz Sheikh; Asher Fawad; Muhammad A. Haleem (Metabolic Brain Disease, 2017)

Environment polluting conventional chemical control compared to an environmentally friendly IPM approach for control of diamondback moth, Plutella xylostella (L.), in China: a review - Muhammad Shakeel; Muhammad Farooq; Wajid Nasim; Waseem Akram; Fawad Zafar Ahmad Khan; Waqar Jaleel; Xun Zhu; Haichen Yin; Shuzhong Li; Shah Fahad; Saddam Hussain; Bhagirath Singh Chauhan; et al. (Environmental Science and Pollution Research, 2017)

Remediation of arsenic-contaminated water using agricultural wastes as biosorbents - Muhammad Bilal Shakoor; Nabeel Khan Niazi; Irshad Bibi; Ghulam Murtaza; Anitha Kunhikrishnan; Balaji Seshadri; Muhammad Shahid; Shafaqat Ali; Nanthi S. Bolan; Yong Sik Ok; Muhammad Abid; Fawad Ali (Critical Reviews in Environmental Science and Technology, 2016)